Zarządzanie ewaluacją inwestycji niekomercyjnych - Kopińska, Joanna (Management of non-commercial investments evaluation, 2006)
This paper explains the nature and presents the essential aspects of evaluation management as far as non-commercial investments are concerned, focusing mostly on EU structural funds. The beginning of the paper summarises the importance of the problem especially for Poland, which has recently entered the European Union. The aim of the central part of the article is to describe the nature of the evaluation process in contrast with the definitions of „monitoring” and „control”. Subsequently, the paper attempts to explain the development of the evaluation potential in the united Europe, focusing also on various approaches towards evaluation. The final and the crucial part concentrates on the basics of evaluation management as well as the procedures practised by the European Commission in the field of structural funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 180-188